Respostas
respondido por:
1
Resposta:
S = {(29/11, -9/11)}
Explicação passo-a-passo:
respondido por:
0
Resposta:
2x - 7y = 11
3x + 6y = 3
Isolando o x na primeira equação:
2x = 11 + 7y
x = (11 + 7y)/2
Substituindo o x na segunda equação:
3x + 6y = 3
3(11 + 7y)/2 + 6y = 3
(33 + 21y)/2 + 6y = 3
(33 + 21y + 12y)/2 = 3
(33 + 33y)/2 = 3
33 + 33y = 6
33y = 6 - 33
33y = -27
y = -27/33
y = -9/11
Substituindo y na primeira equação:
2x - 7(-9/11) = 11
2x + (63/11) = 11
(22x + 63)/11 = 11
22x + 63 = 121
22x = 121 - 63
22x = 58
x = 58/22
x = 29/11
x = 29/11
y = -9/11
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás